Developing a system of innovation - Albert, Sylvie; Mcleod, Al (Henry Stewart Talks, 2023)
VUCA Environment, Adaptability, Creativity vs. Innovation, Building Capability, The Innovation Portfolio, Complexity, The Turner Model, Innovation Engineering (IE), Search for Stimulus, FERMI Estimating, ASPIRE Competency Centre Model